Self-esteem and peer pressure susceptibility mediating the link between maternal behavior and adolescent risk behaviors - Milić, Marija; Bjelobrk, Vladimir; Šincek, Daniela (Frontiers in Psychology, 2025)
IntroductionEarly adolescence is a crucial period of change, during which some youths begin to engage in externalizing and internalizing risk behaviors. Prevention at an early stage is vital to prevent more serious issues later. Although parental influence decreases and peer influence increases during this time, parental behavior still plays a significant role. This study examined the impact of parenting psychological control and warmth on the occurrence of risk behaviors in early adolescence, with susceptibility to peer pressure and self-esteem serving as potential mediators.MethodsThe sample consisted of 410 eighth-grade students with an average age of 14 years. The instruments used were the Scale of Perception of Family Relationships, Susceptibility to Peer Pressure Scale, Rosenberg Self-Esteem Scale, and two subscales assessing risk-taking behavior among youth, which are part of the Self-Reported Risk and Delinquent Behavior Questionnaire.ResultsThe findings indicate that while models with both mediators included were confirmed, those in which peer pressure susceptibility mediated the relationship between parental behaviors and mild externalizing risk behaviors demonstrated a better fit. In contrast, in the relationship between parental behavior and internalizing risk behaviors, self-esteem emerged as a more effective mediator. All models showed partial mediation, indicating that only a portion of the influence of parenting behavior on the occurrence of risk behaviors is accounted for by these mediators. Analyses presented here focus on maternal data, with paternal results showing highly similar patterns.DiscussionThe contribution of this study lies in the finding that parental warmth and psychological control and the development of mild externalizing and internalizing risk behaviors are mediated in somewhat different ways with respect to self-esteem and susceptibility to peer pressure. Aside from scientific implications, these results also have practical implications, as they suggest more concrete intervention strategies that can be implemented in family and school settings to mitigate risk behaviors.